203k views
3 votes
Solve. 5(y - 10) = -5 Answer: Submit Answer att

User Ciso
by
6.9k points

1 Answer

3 votes
Solving an equation

Step 1

We divide both sides by 5 so we can eliminate the parenthesis:


\begin{gathered} 5(y-10)=-5 \\ (5(y-10))/(5)=-(5)/(5) \\ y-10=-1 \end{gathered}

Step 2

We rearrange the terms so the terms with the unkown variable y are on the left side and the other ones on the right side:

y - 10 = -1

adding 10 both sides

y - 10 + 10 = -1 + 10

y + 0 = 9

y = 9

Answer: y = 9

User Asvignesh
by
6.4k points